Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/ecs2.1778
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of distributional asymmetry in a warming environment: invasion of novel forests by the mountain pine beetle

Abstract: Abstract. The range of many Holarctic forest insects does not comprise the entire range of their hosts, as they are often limited to more southern latitudes by the adverse effects of cold temperatures. Global climate warming has led to the increased potential for forest insects to invade novel habitats of native hosts within the same landmass. The mountain pine beetle (MPB; Dendroctonus ponderosae) has recently expanded into higher-latitude forests of the principal host, lodgepole pine (Pinus contorta var. lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 98 publications
0
24
1
Order By: Relevance
“…Local adaptation can have both climate and many nonclimate components, including other abiotic factors such as soil and photoperiod (Savolainen et al 2013, Christmas et al 2016a, but biotic factors such as antagonists and mutualists are also important (Crémieux et al 2008, Gellie et al 2016, Gehring et al 2017, Urbina et al 2018. Some nonlocal provenances may have no history of exposure to local pests and pathogens (Potts et al 2016), and pests and pathogens may themselves be shifting their ranges (Burke et al 2017), potentially increasing the risk of maladaptation (Gellie et al 2016). Little is known about the relative importance of climate compared with these other factors for most plant species, but reciprocal transplant and experimental treatments (e.g., herbivore and pathogen exclusion or exposure trials) can help tease these effects apart.…”
Section: Research Prioritiesmentioning
confidence: 99%
“…Local adaptation can have both climate and many nonclimate components, including other abiotic factors such as soil and photoperiod (Savolainen et al 2013, Christmas et al 2016a, but biotic factors such as antagonists and mutualists are also important (Crémieux et al 2008, Gellie et al 2016, Gehring et al 2017, Urbina et al 2018. Some nonlocal provenances may have no history of exposure to local pests and pathogens (Potts et al 2016), and pests and pathogens may themselves be shifting their ranges (Burke et al 2017), potentially increasing the risk of maladaptation (Gellie et al 2016). Little is known about the relative importance of climate compared with these other factors for most plant species, but reciprocal transplant and experimental treatments (e.g., herbivore and pathogen exclusion or exposure trials) can help tease these effects apart.…”
Section: Research Prioritiesmentioning
confidence: 99%
“…Such changes in distribution patterns have been widely reported in Lepidoptera (Parmesan et al, 1999;Battisti et al, 2005Battisti et al, , 2006Wilson et al, 2005Wilson et al, , 2007Franco et al, 2006). Other examples include the northward spread of the mountain pine beetle Dendroctonus ponderosae (Coleoptera: Curculionidae) (Weed et al, 2015;Burke et al, 2017) and Dendroctronus frontalis (Coleoptera: Scolytidae) (Ungerer et al, 1999), all in response to winter warming. Such evidence in parasitoids is scant.…”
Section: Climate Change Impacts On Biogeography and Parasitoid-host Imentioning
confidence: 79%
“…In contrast, a significant induced defensive reaction from the MeJa treatment was not detected for the majority of terpenes. This may be because MeJa does not induce a defensive reaction in the same manner, or as extensively, as actual MPB infestation [ 20 ]. In addition, previous work has found that resistant trees undergoing induced defense had higher levels of both limonene and terpinolene than those that were less resistant [ 32 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Defensive reactions within lodgepole pines and other conifers can be artificially induced by the application of the phytohormone, methyl jasmonate (in the form of MeJa, the volatile derivate of jasmonic acid), which causes an induced stress response in plants via the regulation of gene expression, to reallocate energy from photosynthesis and growth to secondary metabolite production [ 13 , 16 , 19 ]. Further, this MeJa-induced response produces many of the same anatomical changes in conifers as that of mechanical wounding meant to mimic bark beetle attack [ 16 ], although the defensive monoterpene response from MeJa is more generalized and quantitatively different than that of simulated bark beetle attacks consisting of both mechanical wounding and fungal inoculation [ 20 ].…”
Section: Introductionmentioning
confidence: 99%